Comparison of the relative muscle volume of triceps surae among sprinters, runners, and untrained participants - Atsuki Fukutani (Physiological Reports, 2020)
Abstract Muscle hypertrophy is considered more prominent in fast‐twitch than in slow‐twitch muscles. This leads to the hypothesis that the relative muscle volume of the medial gastrocnemius (MG) and lateral gastrocnemius (LG) becomes larger than that of the soleus (SOL) in highly trained participants because MG and LG include more fast‐twitch muscles than SOL. Thus, we compared relative muscle volume among highly trained sprinters, long‐distance runners, and untrained participants to examine whether the above hypothesis is correct. Magnetic resonance imaging was used to calculate the muscle volume of MG, LG, and SOL from 126 participants. The total muscle volume of the three muscles and the relative muscle volume of each muscle with respect to the total muscle volume were calculated. The total muscle volume was significantly larger in the sprinters than in the long‐distance runners and untrained participants. The relative muscle volume of MG was significantly larger in the sprinters than in the long‐distance runners and untrained participants and that of SOL was significantly smaller in the sprinters than in the long‐distance runners and untrained participants. These results indicate that the relative muscle volume can vary among participants, possibly due to fiber type‐dependent muscle hypertrophy.